Reviews of Environmental Contamination and Toxicology Volume 217 - Whitacre, David M.; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
CONTENTS Foreword Preface Chiral Pesticides: Identification, Description, and Environmental Implications Elin M. Ulrich, Candice N. Morrison, Michael R. Goldsmith, and William T. Foreman Strategies for Chromium Bioremediation of Tannery Effluent Satyendra Kumar Garg, Manikant Tripathia and Thiruneelakantan Srinath Index
Foreword -- Preface -- Chiral Pesticides: Identification, Description, and Environmental Implications -- Strategies for Chromium Bioremediation of Tannery Effluent -- Index.
Keywords: Environmental sciences; Environmental management; Environmental toxicology; Waste disposal; Environment; Ecotoxicology; Environmental Management; Waste Management/Waste Technology